Association of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and chronic kidney disease in elderly insights from NHANES - Yifan Sun; Zhou Li; Ninghan Feng (Scientific Reports)
Abstract The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a novel lipid index. Prior research has established a connection between lipid irregularities and chronic kidney disease (CKD). This study aims to establish a possible link between NHHR and CKD. Data from the National Health and Nutrition Examination Survey (NHANES) spanning from 2003 to 2016 was used to examine the relationship between NHHR and CKD among the elderly population. This research utilized weighted logistic regression, smoothed curve fitting and subgroup analyses along with interaction tests to evaluate the association between NHHR and CKD. The findings reveal a positive correlation between NHHR and CKD in fully adjusted Model 3. Besides, NHHR had a J-curve relationship with CKD. Subgroup analysis indicated that compared with those with lower body mass index (BMI), individuals with higher BMI are more prone to CKD. Research has shown that increased NHHR levels are associated with a higher likelihood of developing CKD in individuals aged above 60 in the United States. NHHR’s role in lipid metabolism suggests it might be an effective marker for tracking CKD’s progression.